The Effect of Internal Control Systems on Financial Performance of Small and Medium Enterprises in Mukono Municipality, Uganda: A Case of Paris Corner Supermarket Ltd and City Shoppers Supermarket Ltd - Wilber Akanyijuka (Uganda Christian University, 2023)
The purpose of the study was to assess the effect of internal control systems on financial performance of small and medium enterprises in Mukono Municipality in Uganda. The study was guided by the following research questions; What is the effect of risk assessment on the financial performance of SMEs in Mukono Municipality, Uganda? What is the effect of monitoring on the financial performance of SMEs in Mukono Municipality, Uganda? What is the effect of internal audit on the financial performance of SMEs in Mukono Municipality, Uganda? The study used a case study of Paris Corner Supermarket Ltd and City Shoppers Supermarket Ltd. The total population of 71 staff (management and employees) was targeted for the study though 89% (63 staff) managed to respond. Primary data was collected was collected using structured questionnaires and conducting interviews. Primary data was collected using structured questionnaire. Statistical Package for Social Sciences (SPSS) computer software program was used in analyzing the data. Quantitative data was analyzed and the output was presented using a descriptive statistic of percentages. Qualitative data was analyzed and the output was presented by narration. The respondents agreed that risk assessment is efficient and effective in minimizing financial losses of their company and that monitoring is effective to the financial performance of their company. Further, majority of the respondents disagreed that their company has an internal audit function. The study concludes that absence of internal audit exposes SMEs to financial risk. This study concludes that there exists a significant relationship between internal control systems and financial performance of SMEs in Mukono Municipality in Uganda. The study also recommends that SMEs be transparent on the risk assessment control system to the employees since they form part of the company structure and are directly involved with the hands-on activities.
This is a dissertation